PENDIDIKAN MULTIKULTURALISME DALAM PERSPEKTIF ISLAM - Listanti, Hani; Tsaniyyah, Ulwatul; Puspika Sari, Herlini (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to examine multicultural education from an Islamic perspective. As we know, multicultural education is an approach that emphasizes the importance of acknowledging and valuing diversity in culture, ethnicity, religion, and values within society. From the perspective of Islam, multicultural education is not merely a social process but also a reflection of justice, tolerance, and brotherhood, values taught in the Qur’an and Hadith. Islam teaches that differences are a sunnatullah (divine wisdom) to be embraced wisely as the richness of humanity, not as a source of conflict. The aim of this paper is to investigate and analyze how the values of multicultural education are embedded within Islamic teachings and their relevance in the context of modern education. The method employed is a qualitative-descriptive literature review, gathering various primary and secondary sources on education, multiculturalism, and Islamic values. The findings show that Islamic educational principles such as ukhuwah (brotherhood), tasamuh (tolerance), ta’aruf (mutual acquaintance), and justice closely align with the values of multicultural education. By applying a multicultural education approach grounded in Islamic values, educational institutions can serve as platforms for developing inclusive and moderate character, capable of reducing potential social conflicts. Therefore, multicultural education based on Islamic values is highly relevant for development in Indonesia’s pluralistic society, supporting social harmony and strengthening national integration.